Dimensioning Silicone Joints Used in Bomb Blast Resistant Facade Systems - Pierre Descamps (Challenging Glass Conference, 2018)
In the design of blast resistant glazing systems, gluing the laminate glass to the window frame with a structural adhesive is an attractive option to maintain it attached to the frame while, because the large deflection of the broken laminate, it could potentially escape from a mechanical fixing. Actually, it does not exist a simple method that provides guidelines to the facade maker to design a joint that will resist to a blast. The complexity to develop such a method is due to 1) the blast load is time dependent and the phase shift between the external load and the natural mode of vibration of the pane must be included in the model 2) modeling the deformation of a laminated glass after breakage of glass plies is complex. The intend of this study is not to propose the most accurate description of both the laminate and the joint deformation under a blast load but to identify which assumptions could be possibly made to simplify the problem and make possible the derivation of a simplified joint dimensioning method.